Analysis of school authorities´ concepts and suggestions on bullying - doi: 10.4025/actascieduc.v36i1.21940 - José Leon Crochík; Pedro Fernando Silva; Cintia Copit Freller; Lucas Stefano de Lima Alves; Aline Costa Carrenho; Gianlucca Vergian Dalenogare (Universidade Estadual de Maringá, 2014)
Interviews by school authorities from five public primary schools inSão Paulo,São Paulo State,Brazilwere analyzed. The contents of the interviews by school principals and pedagogical coordinators investigated (1) the manner they understood bullying, especially with regard to their determinations; (2) their proposals for combating the problem; (3) the relationship between their understanding of the phenomenon and the suggestions against it. Results showed that the authorities that perceived the social determination on school violence had the best structured suggestions against the phenomenon, with regard to its understanding by students and teachers. On the other hand, others, foregrounded on a more reductionist stance which made difficult the perception of bulling within the school milieu, suggested activities which were not relevant to the factors that produced it and thus not efficacious in their attacking the phenomenon.